Primeiro tratado brasileiro de psico-oncologia - Gonçalves, Camila Salles (Percurso, 2011)
Resenha de Vicente Augusto de Carvalho, Maria Helena Pereira Franco, Maria Julia Kovács, Regina Paschoalucci Liberato, Rita de Cássia Macieira, Maria Teresa Veit, Maria Jacinta Benites Gomes, Luciana Holtz de C. Barros (orgs.), Temas em psico-oncologia, São Paulo, Summus, 2008, 645 p.